2024
DOI: 10.3390/su16052137
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Model for Sustainability Assessment of Chemical Analyses Laboratories in Public Higher Education Institutions

Marco Antonio Souza,
Mario Orestes Aguirre González,
André Luís Santos de Pinho

Abstract: The increasing demand for sustainable products and services has become a constant requirement for the different stakeholders in an organization. Higher Education Institutions (HEI) have a crucial role in training conscious and competent professionals to lead these changes. Chemical analyses laboratories bring together the proper mix, where the adoption of mature and efficient management systems proves to be crucial not only to better train the institutions’ human resources but also to cooperate in recruiting r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The maturity model is used to assess the state of a company or a production organization under one of the states indicated by such models. This concept could include business process management [35], [36], inventory management [37], supply chain management [38], [39], new product development [40], R&D projects [41], project management [42], quality management [43], sustainability [44], [45], [46], service innovation [47] and service management [48], [49]. They may be used to obtain helpful information regarding the point of departure for improving the processes of extant organizations [50] or to compare different organizations [33].…”
Section: Maturity Modelmentioning
confidence: 99%
“…The maturity model is used to assess the state of a company or a production organization under one of the states indicated by such models. This concept could include business process management [35], [36], inventory management [37], supply chain management [38], [39], new product development [40], R&D projects [41], project management [42], quality management [43], sustainability [44], [45], [46], service innovation [47] and service management [48], [49]. They may be used to obtain helpful information regarding the point of departure for improving the processes of extant organizations [50] or to compare different organizations [33].…”
Section: Maturity Modelmentioning
confidence: 99%
“…As for the PDP, [4], organizations from countries that classify themselves as developed usually make use of the innovative aspect of new products as a strategy to circumvent the problem of economic crises or increase their revenues, which consequently contributes to an increase in market performance, from the increase in the product portfolio. The authors of [5,6], see that new business competition is focused on the development of new products; therefore, it forces this area to be dynamic and flexible in organizations [7]. In the view of [8,9], it is reported that the process of developing new products is a risky activity because, just as it can bring about success, being converted directly into profits for the company, it can also be a failure, which is implied in lost expenses and investments.…”
Section: Introductionmentioning
confidence: 99%